Vowel confusion patterns in adults during initial 4 years of implant use. - Väälimaa TT; Sorri MJ; Laitakari J; Sivonen V; Muhli A (Clinical Linguistics & Phonetics, 2011)
This study investigated adult cochlear implant users' ( n == 39) vowel recognition and confusions by an open-set syllable test during 4 years of implant use, in a prospective repeated-measures design. Subjects' responses were coded for phoneme errors and estimated by the generalized mixed model. Improvement in overall vowel recognition was highest during the first 6 months, showing statistically significant change until 4 years, especially for the mediocre performers. The best performers improved statistically significantly until 18 months. The poorest performers improved until 12 months and exhibited more vowel confusions. No differences were found in overall vowel recognition between Nucleus24M//24R and Med-ElC40++ device users (matched comparison), but certain vowels showed statistically significant differences. Vowel confusions between adjacent vowels were evident, probably due to the implant users' inability to discriminate formant frequencies. Vowel confusions were also dominated by vowels whose average F1 and//or F2 frequencies were higher than the target vowel, indicating a basalward shift in the confusions.